The effect of students dropping out of secondary schools on their cognitive outcome and attitude towards learning from the point of view of their teachers - Al-Qarinawi, Ayoub Suleiman Salama; Al-Qashala, Badi Aziz (Journal of Educational and Psychological Sciences, 2025)
The study aimed to determine the effect of students dropping out of secondary schools on their cognitive outcome and attitude towards learning from the point of view of their teachers. In addition to determining whether there are statistically significant differences in the degree of response of the study sample members to the impact of students dropping on cognitive achievement and attitude towards learning attributed to demographic variables (gender, experience). To achieve the objective of the study, the descriptive analytical approach was followed, and the questionnaire was used as a tool to collect data from the study sample of (45) male and female teachers of government schools in the State of Palestine, out of (110) male and female teachers representing the study population. The results showed that: 1.The impact of students dropping out of secondary schools on their cognitive outcome and attitude towards learning from the point of view of their teachers was high.2. The results also showed that there were no statistically significant differences at the significance level (α=0.05) in the study sample’s response to the tool due to the gender variable and in favor of the female group, while there were no statistically significant differences at the significance level (α=0.05) in the study sample’s response. The tool is attributed to the variable of experience, and in light of the results.The study recommends holding training courses for all elements of the educational process to demonstrate the effects of school dropout on all elements of society.